2013
DOI: 10.1016/j.phytochem.2013.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive steroidal saponins from Agave offoyana flowers

Abstract: Bioguided studies of flowers of Agave offoyana allowed the isolation of five steroidal saponins never described previously, Magueyosides A-E (1-5), along with six known steroidal saponins (6-11). The structures of compounds were determined as (25R)-spirost-5-en-2α,3β-diol-12-one 3-O-{β-d-xylopyranosyl-(1→3)-O-β-d-glucopyranosyl-(1→2)-O-[β-d-xylopyranosyl-(1→3)]-O-β-d-glucopyranosyl-(1→4)-O-β-d-galactopyranoside} (1), (25R)-spirost-5-en-2α,3β-diol-12-one 3-O-{β-d-glucopyranosyl-(1→2)-O-[β-d-xylopyranosyl-(1→3)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 58 publications
6
71
0
2
Order By: Relevance
“…The majority of the extraction procedures for saponins of Agave involve classical methods such as Soxhlet extraction (Wilkomirski et al, 1975) and maceration (Chen et al, 2011;Eskander et al, 2010;Perez et al, 2013Perez et al, , 2014Yokosuka and Mimaki, 2007). The choice of the extraction solvents is also limited as the saponins dissolve in polar solvents only.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the extraction procedures for saponins of Agave involve classical methods such as Soxhlet extraction (Wilkomirski et al, 1975) and maceration (Chen et al, 2011;Eskander et al, 2010;Perez et al, 2013Perez et al, , 2014Yokosuka and Mimaki, 2007). The choice of the extraction solvents is also limited as the saponins dissolve in polar solvents only.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…subcerulata (leaves) Blunden et al (1980b) A. cocui (leaves) Blunden et al (1980b) Sharma and Khanna (1980) A. filifera (leaves) Blunden et al (1978) A. avellanidens (leaves) Blunden et al (1980b) A. cerulata (leaves) Blunden et al (1980b) A. cerulata ssp. subcerulata (leaves) Blunden et al (1980b) A. cocui (leaves) Blunden et al (1980b) A. canatala (leaves) A. wightii (leaves) Khanna et al (1979) 16 (25S)-5a-Spirostan-3-one (Neotigogenone) A. sisalana (leaves) Tsung et al (1976a) 17 (25R)-5b-Spirostan-3b-ol (Smilagenin) A. lecheguilia (leaves) Blunden et al (1980a);de Rodriguez et al (2006) A. haynaldii (leaves) Blunden et al (1978) A. rigidissima (leaves) Blunden et al (1978) A. ghiesbrechtii (leaves) Blunden et al (1974) 18 (25S)-5b-Spirostan-3b-ol (Sarsasapogenin) A. attenuata (leaves) Blunden et al (1978); Mendes et al (2004) A. lophantha (leaves) Bedour et al (1979) 19 (25R)-5b-Spirostan-3b,6a-diol (Ruizgenin) A. lecheguilia (leaves) Blunden et al (1980a) (25S)-5a-Cholestane-3b,16b,22b,26-tetrol (Agavegenin D) A. americana (leaves) Jin et al (2004a) methanol (or ethanol)-water combinations (Perez et al, 2013(Perez et al, , 2014Yu et al, 2011) are generally employed for extraction. The choice of solvent also depends upon the probability of artifact formation.…”
mentioning
confidence: 99%
“…Mass spectra analysis of compound 2 showed that two kammogenin glycosides were co-eluting. These saponins exhibited characteristic ions at m/z 1217.51 ([M + Na] + ) and 1085.48 ([M + Na] + ), and both were isolated previously from flowers of A. offoyana and identified as magueyoside A and magueyoside B, respectively [16]. Similarly, at the retention time of compound 4, two kammogenin glycosides were found.…”
Section: Metabolomicsmentioning
confidence: 85%
“…Concentrations were reported as µg PE/mg extract. For saponin characterization, extracted ion chromatograms were analyzed considering the exact masses reported for saponins and sapogenins, as well as their fragmentation patterns (±0.05 units) using the Analyst QS 1.1 software (Applied Biosystems) [6,7,16].…”
Section: Metabolomics and Saponins Analysis By Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation